MANAGEMENT OF COTTON BUD INDUCED OTITIS EXTERNA BY UNIQUE METHOD - Bukhari, Syed Muhammad Asad Shabbir; Aslam, Sohail; Riaz, Naeem; Ayub, Muhammad Waqas; Saeed, Irfan; Asghar, Adnan; Khan, Muhammad Fahad Wasim (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the recovery of patients in both groups having acute otitis externa induced by cotton buds/various objects. One group by old method and second group by unique method.Study Design: Quasi-experimental study.Place and Duration of Study: Pakistan Naval Ship Shifa Karachi, from Jan to Dec 2020.Methodology: Non-probability convenience sampling technique was applied. Out of 50 cases were selected for group 1 management. Fifty cases were selected for group 2 management. A chi-square test was applied to compare the recovery of two groups of patients on the 14th day and 42nd day of follow-up. p-value was kept 0.05 as significant.Results: A total of 100 cases were treated in 2 groups. The gender distribution of the study was 54 females and 46 males. The mean age of the study population was 33.09 ± 12.93 years. p-value was calculated on the 14th day and 42nd days. A 2x2 table of 14th follow up day showed recovery by both groups with a p-value of 0.041 which is